Brainstem response to hypercapnia: A symptom provocation study into the pathophysiology of panic disorder. (May 2014) - Goossens, Liesbet; Leibold, Nicole; Peeters, Ronald; Esquivel, Gabriel; Knuts, Inge; Backes, Walter; Marcelis, Machteld; Hofman, Paul; Griez, Eric; Schruers, Koen
Background: The biological basis of uncued panic attacks is not yet understood. An important theory concerning the nature and cause of panic disorder is the 'suffocation false alarm theory'. This alarm is supposed to be over-sensitive in panic disorder patients and can be triggered by CO2 . No neurobiological substrate has been identified for such an alarm. The present study investigates differences in brain activation in panic patients, healthy individuals and experienced divers in response to CO2, representing three groups with descending sensitivity to CO2 . Method: Brain activation was measured with functional magnetic resonance imaging. Subjects breathed through a mouthpiece delivering a continuous flow of 100% oxygen for two minutes, followed by a hypercapnic gas mixture (7% CO2 ) for the next two minutes. Statistical analysis was performed using SPM8. Results: There was a significant main effect of group in response to the CO2 . Patients show increased brainstem activation in response to hypercapnia compared to controls and divers. Subjective feelings of breathing discomfort were positively correlated with brain activation in the anterior insula in all groups. Conclusion: This is the first study showing that the behavioural response to CO2 that characterises panic disorder patients is likely due to increased neural sensitivity to CO2 at brainstem level.